Investigation the Relationship between Intrinsic Motivation and Creative Production on Solving Real Problems - Nair, Subadrah; Alkiyumi, Mohammed T (SOSIOHUMANIKA, 2011)
ABSTRACT: This study was designed to investigate whether Intrinsic Motivation (IM) related to the creative production on solving real problems that measured based on two criteria: novelty and appropriateness. 10th-grade students in Oman represented by 367 students (male and female) from eight schools (rural and urban) were the sample of the study. Work Preference Inventory from T.M. Amabile, B. Hennessy and E. Tighe (1994) was manipulated to assess intrinsic motivation. Problem-Solving Test (PST) developed by researchers was used to measure creative production on solving real problems through content contexts of subjects such as Arabic Language, Social Studies, and Science. Findings showed that IM correlated positively with novelty and appropriateness. MANOVA test showed that main effect of school type was significant for novelty and appropriateness, but gender was not. Analysis of simultaneous regression indicated that intrinsic motivation and gender predicted the total score of problem solving test, but school type was not. The implications of the study enhance our understanding of the intrinsic motivation as a personality trait on developing creativity among school students.Key words: Intrinsic motivation, creative production, solving real problems, novelty and appropriateness, and students in Oman.Â Â About the Authors: Assoc. Prof. Dr. Subadrah Nair and Mohammed T. Alkiyumi are a Senior Lecturer and a Ph.D. Candidate at the School of Educational Studies USM (Science University of Malaysia), 11800 Minden, Pulau Penang, Malaysia. They can, for academic matters, be contacted at: subadrah@usm.my and alkeumi@gmail.comHow to cite this article? Nair, Subadrah & Mohammed T. Alkiyumi. (2011). âInvestigation the Relationship between Intrinsic Motivation and Creative Production on Solving Real Problemsâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.4, No.2 [November], pp.185-196. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-0112. Chronicle of article: Accepted (September 9, 2011); Revised (October 13, 2011); and Published (November 20, 2011). Â  Â